Long-lasting improvements in episodic memory among subjects with mild cognitive impairment who received transcranial direct current stimulation combined with cognitive treatment and telerehabilitation: a multicentre, randomized, active-controlled study - Manenti, Rosa; Baglio, Francesca; Pagnoni, Ilaria; Gobbi, Elena; Campana, Elena; Alaimo, Cristina; Rossetto, Federica; Di Tella, Sonia; Pagliari, Chiara; Geviti, Andrea; Bonfiglio, Natale Salvatore; Calabrò, Rocco Salvatore; et al. (Frontiers in Aging Neuroscience, 2024)
Background: In recent years, an increasing number of studies have examined the potential efficacy of cognitive training procedures in individuals with normal ageing and mild cognitive impairment (MCI). Objective: The aims of this study were to i) evaluate the efficacy of the cognitive virtual reality rehabilitation system (VRRS) combined with anodal transcranial direct current stimulation (tDCS) applied to the left dorsolateral prefrontal cortex compared to placebo tDCS stimulation combined with VRRS and ii) to determine how to prolong the beneficial effects of the treatment. A total of 109 subjects with MCI were assigned to 1 of 5 study groups in a randomized controlled trial design: (a) face-to-face (FTF) VRRS during anodal tDCS followed by cognitive telerehabilitation (TR)